2019
DOI: 10.1039/c9qi00547a
|View full text |Cite
|
Sign up to set email alerts
|

N-Methyl-2-pyrrolidone as an excellent coordinative additive with a wide operating range for fabricating high-quality perovskite films

Abstract: N-Methyl-2-pyrrolidone (NMP), forming only one PbI2·NMP complex, is demonstrated as an excellent coordinative solvent for the fabrication of high-quality perovskite thin films.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 36 publications
1
20
0
Order By: Relevance
“…[ 35 ] On the other hand, PbI 2 .NMP (Figure 1g) consists of double‐chains of edge‐sharing PbI 5 O octahedra with unshared apexes stabilized by NMP coordinated with Pb atoms, similar to PbI 2 (DMSO). [ 37,38 ] In other words, the intermediate formed using NMP does not present any contribution from MA molecules differently from the DMSO intermediate. The Gutmann acceptor donor number (DN) measures the strength of the solvents as Lewis bases.…”
Section: Resultsmentioning
confidence: 99%
“…[ 35 ] On the other hand, PbI 2 .NMP (Figure 1g) consists of double‐chains of edge‐sharing PbI 5 O octahedra with unshared apexes stabilized by NMP coordinated with Pb atoms, similar to PbI 2 (DMSO). [ 37,38 ] In other words, the intermediate formed using NMP does not present any contribution from MA molecules differently from the DMSO intermediate. The Gutmann acceptor donor number (DN) measures the strength of the solvents as Lewis bases.…”
Section: Resultsmentioning
confidence: 99%
“…These two φ phases are related to the formation of PbI 2 complexes involving the solvent molecules, PbI 2 ─DMF and PbI 2 ─NMP. [30,32,37] Interestingly, these diffraction peaks gradually disappear with the addition of MACl into the precursor solution. Such a phenomenon was noticed by Li et al, [38] who identified an identical trend, for double-cation MA/FA deposition, by spin coating.…”
Section: Crystallization Differences Between Vacuum Extraction and Antisolvent Methodsmentioning
confidence: 99%
“…[26] In this work, we focused on a double-cation (FA 0.83 Cs 0.17 )/ double-anion (I 0.83 Br 0.17 ) 3 perovskite composition better suited to tandem applications due to its high-bandgap value (E g ¼ 1.64 eV) compared with MAPbI 3 counterpart. Engineering of the ink formulation by the introduction of methylammonium chloride (MACl), [27][28][29] together with N-Methyl-2-pyrrolidone (NMP), [30][31][32] is herein studied, these additives being known to influence the crystal growth. Based on a holistic optimization of the triptych constituted by ink formulation, the slot-die deposition parameters, and the vacuum drying process, we achieved pinhole-free deposition on a large area (5 Â 10 cm 2 ) of Cs 0.17 FA 0.83 Pb(I 0.83 Br 0.17 ) 3 perovskite films.…”
Section: Introductionmentioning
confidence: 99%
“…In an investigation, Zhang and co-workers demonstrated that NMP as a solvent additive (when added in DMF) resulted in a high quality of perovskite film due to the Lewis acid-base reaction with Pb atom. The study revealed that intermediates obtained with different PbI 2 /NMP ratios are of the same kind, because of which, the solar cell performance and stability do not depend on the NMP ratio in the precursor [51]. Following the idea of the Lewis acid-base interaction, KIM and co-workers explored pyrrolidone-based solvent additives and compared with commonly used DMF-based precursor [52].…”
Section: N Donor Atom-based Additives 211 Amine Additivesmentioning
confidence: 99%